2012
DOI: 10.4021/jcgo44w
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Inflammatory Response in Severe Preeclamptic and Preeclamptic Pregnancies

Abstract: Background: The aim of this study was to use serum levels of IL-6, IL-8, IL-1β, TNF-α, CD40L and HSCRP as an in vitro inflammatory stimulus in order to profile the inflammatory response of whole blood from pregnant women with preeclampsia and severe preeclampsia, and to determine whether this functional response fits with imbalance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 28 publications
0
5
0
2
Order By: Relevance
“…31,32 Hence, our findings that hypoxic treatment of the dual placental perfusion system produces significantly higher levels of TNF-a and IFN-g closely parallel the in vivo response in preeclampsia. Furthermore, both IL-6 and IL-8 are found to be significantly increased in preeclampsia, 33,34 and both these pro-inflammatory cytokines were also secreted at a significantly increased rate under hypoxic treatment of the dual placental perfusion system compared with the normoxic group. As there are very few maternal lymphatic cells present in this system, this response to hypoxia most likely originates from the placental trophoblast.…”
Section: Discussionmentioning
confidence: 92%
“…31,32 Hence, our findings that hypoxic treatment of the dual placental perfusion system produces significantly higher levels of TNF-a and IFN-g closely parallel the in vivo response in preeclampsia. Furthermore, both IL-6 and IL-8 are found to be significantly increased in preeclampsia, 33,34 and both these pro-inflammatory cytokines were also secreted at a significantly increased rate under hypoxic treatment of the dual placental perfusion system compared with the normoxic group. As there are very few maternal lymphatic cells present in this system, this response to hypoxia most likely originates from the placental trophoblast.…”
Section: Discussionmentioning
confidence: 92%
“…Peningkatan sitokin pro-inflamasi juga diperlukan untuk merangsang produksi MMP-1, MMP-3, MMP-9 yang diperlukan untuk pematangan servik. 16 Pada akhir kehamilan normal juga terjadi peningkatan respon inflamasi yang berperan untuk persiapan persalian begitu juga yang terjadi pada preeklampsia tipe lambat. Pada wanita yang memiliki maternal konstitusi terjadi peningkatan ambang batas inflamasi, sehingga dengan adanya inflamasi kronik dengan intensitas rendah dapat menyebabkan timbulnya gejala preeklampsia.…”
Section: Interleukin-10 Pada Kehamilan Normalunclassified
“…Studi lain menunjukkan amplifikasi inflamasi pada preeklampsia oleh aktivasi sistem komplemen. 16,17 Teori inflamasi dan preeklampsia dari Redman dan Sargent membagi preeklampsia menjadi plasental dan maternal. Pada wanita normal, meskipun kehamilan normal dapat merangsang respon inflamasi sistemik, tetapi hal itu tidak cukup untuk menimbulkan pre-eklampsia.…”
Section: Interleukin-10 Pada Preeklampsiaunclassified
“…Complete failure of this mechanism would cause miscarriage, while partial failure would cause poor placentation and dysfunctional uteroplacental perfusion [8]. Bayram et al found that the patient with severe preeclampsia have higher values of IL-6 and IL-1β when compared to the normotensive ones [9]. Increased level of IL-6 and TNF-α may play a role of triggering factors for preeclampsia.…”
Section: Introductionmentioning
confidence: 99%